Analisis Analisis Determinasi Kualitas Produk dan Nilai Ekonomis terhadap Loyalitas Konsumen DIMSAY (Dimsum Always Yummy) - Mugianto, Maulidia; Kusdiana, Shindi; Febriyanti, Firdya; Fikri H., M. Ammar; Azzhara, Calista Desi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The urban area of ​​Surabaya exhibits intense business competition in the culinary industry, particularly in the sale of dim sum (Dimsay) products. To successfully increase sales volume, businesses must effectively manage customer perceptions of their products and the quality of their service. The purpose of this research is to examine and describe how taste, price level, and service quality impact Dimsay sales growth in Surabaya, both individually and collectively. This research employed quantitative methods through a survey. Data collection was conducted by distributing a questionnaire to 40 respondents, who were frequent Dimsay consumers in Surabaya. The respondents were selected using a purposive sampling technique. The collected data were then analyzed using multiple linear regression to test the validity of the formulated hypotheses. The results of the research show that, in general (through the F test), taste (X1), price (X2), and service quality (X3) have a significant and positive influence on sales growth (Y). When viewed separately (through a t-test), taste and price factors are proven to have a significant influence on sales increases, but the service quality factor does not show a significant influence in this study. The main findings of this study indicate that the taste factor (X1) is the most dominant aspect in influencing customer choices and driving sales increases. This suggests that even though price and service are taken into account, consistency in maintaining taste quality remains the most important element in building customer loyalty in the Dimsay market in Surabaya City